Adults’ Readiness to Learn: Questioning Lifelong Learning for All - Kjell Rubenson (Adult Education Research Conference, 1998)
Lifelong learning for all has become a major policy objective in the industrialized world. This study, which is based on analysis of IALS data, indicates several disturbing trends in the present distribution of lifelong learning. The differences in readiness to learn as an adult can be explained by "the long arm of the family and the long arm of the job." A main conclusion is that Lifelong learning for all is conditional on a working life organized in a way that promotes the use of literacy, and a society where people are encouraged to think, act, and be engaged.